Correlation between the number of breast duct cells expressing androgen, estrogen and progesterone receptors and the size of the changed tissue in patients with gynecomastia - Mladenović, Danilo; Nikolic, Ana; Dundjerovic, Dusko (Medicinski podmladak, 2023)
Introduction: Gynecomastia is an abnormal growth of the male breast due to excessive proliferation of ductal epithelial cells. It usually occurs during puberty, so the influence of hormones on the stimulation of ductal cells is indicative. Androgen, estrogen and progesterone are steroid hormones that exert their influence by binding to intracellular receptors and thus activating transcriptional mechanisms, ie. act as trophic factors. Material and methods:A retrospective study for the period 01.01.2021-31.12.2021 was performed and 6 patients were found, of which in two cases left and right breast gynecomastia surgeries were performed. HE stained slides and corresponding paraffin blocks were taken from the archive, and a tissue microarray was constructed, with 4 tissue cylinders for each tissue sample. Immunohistochemical staining was performed for androgen, estrogen, and progesterone receptors. The all obtained slides were scanned on a Leica Biosystems Aperio AT2 slide scanner, and image analysis was performed in the Aperio Image Scope program. Statistical analysis of the data was performed by the EZR R Commander program. Results:Of the 8 samples, none showed significant androgen receptor expression. Statistical analysis of the number of cells expressing estrogen receptors (ps=0.03676; rho=0.7619048) progesterone (ps=0.002439; rho=0.8982197) and the volume of tissue removed showed a statistically significant positive correlation. Conclusion: The obtained results confirm the hypothesis that the volume of removed breast tissue in patients with gynecomastia correlates with the expression of estrogen and progesterone receptors, but further research on a larger sample is necessary for more reliable conclusions.